Higher concentration of interleukin 6 - A possible link between major depressive disorder and childhood abuse. (June 2018) - Munjiza, Ana; Kostic, Milutin; Pesic, Danilo; Gajic, Milan; Markovic, Ivanka; Tosevski, Dusica Lecic
Highlights: Concentrations of IL-6 were significantly higher in patients with major depressive disorder compared to healthy controls. Depressed patients who were abused had higher levels of IL-6. More specific persons who were physically abused, physically neglected and emotionally abused in childhood had higher levels of IL-6. Our findings may show that the pathway through which childhood abuse raises susceptibility for depression is through long-term alteration of the inflammation response in abused children which is present in adults as well. Abstract: Little is known about the correlation between IL-6 and childhood abuse and neglect which may be risk factors for the development of affective disorders in adulthood. The aim of this study was to analyze differences in serum concentrations of IL-6 between patients with major depressive disorder and healthy controls, and to investigate possible correlations with adverse childhood experiences. Peripheral venous blood samples were obtained from 64 patients who fulfilled DSM-IV-R criteria for a current major depressive episode without psychotic symptoms (MDD) and 53 healthy controls, matched for age and gender. Participants were assessed by the Beck Depression Inventory (BDI), Childhood Trauma Questionnaire (CTQ), Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS). The concentration of IL-6 was significantly higher in patients with major depressive disorder compared to healthy controls. The total score of childhood trauma questionnaire highly statistically significantly correlated with IL-6 levels in patient group. Persons who were physically abused, physically neglected and emotionally abused had higher levels of IL-6. Interleukin 6 as a pro-inflammatory immune marker could be an important developmental mediator linking physical and emotional abuse in early life with the development of depressive disorder in adulthood.